PEDAGOGICAL AND PSYCHOLOGICAL FEATURES OF INTEGRATIVE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE TEACHERS BASED ON DIGITAL TECHNOLOGIES (World Bulletin of Social Sciences, 2023)
This article examines the range of digital competences of teachers by highlighting the key competencies that guarantee their full practical experience. In the empirical study, the self-assessment of the digital competence of the future pedagogues who are being trained in the professional field of pedagogy, as well as the real possibilities of solving specific practical tasks based on the use of information and communication technologies, is distinguished. Some recommendations were given to revise the education of future pedagogical specialists and the professional qualifications of current teachers in the context of the formation and development of their digital competence.